2003
DOI: 10.1103/physrevlett.90.207202
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ferromagnetism in a II-VI Diluted Magnetic SemiconductorZn1xCrxT<

Abstract: The magnetic and magneto-optical properties of a Cr-doped II-VI semiconductor ZnTe were investigated. Magnetic circular dichroism measurements showed a strong interaction between the sp carriers and localized d spins, indicating that Zn(1-x)Cr(x)Te is a diluted magnetic semiconductor. The Curie temperature of the film with x=0.20 was estimated to be 300+/-10 K, which is the highest value ever reported for a diluted magnetic semiconductor in which sp-d interactions were confirmed. In spite of its high Curie tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
190
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(199 citation statements)
references
References 31 publications
9
190
0
Order By: Relevance
“…11 Since the ferromagnetic MCD signal of Co 2+ : ZnO did not resemble that of paramagnetic Co 2+ : ZnO and specifically lacked the 4 A 2 → 4 T 1 ͑P͒ ligand-field feature of substitutional Co 2+ in ZnO, there was speculation that it should be attributed to phase-segregated precipitates. 10 Broad sub-band-gap ferromagnetic MCD features have also been observed in Mn:GaAs, 17 Cr:ZnTe, 18 and Mn:InAs, 19 however, materials for which the intrinsic origins of ferromagnetism are less controversial. We propose that the ferromagnetic MCD signal in Fig.…”
mentioning
confidence: 99%
“…11 Since the ferromagnetic MCD signal of Co 2+ : ZnO did not resemble that of paramagnetic Co 2+ : ZnO and specifically lacked the 4 A 2 → 4 T 1 ͑P͒ ligand-field feature of substitutional Co 2+ in ZnO, there was speculation that it should be attributed to phase-segregated precipitates. 10 Broad sub-band-gap ferromagnetic MCD features have also been observed in Mn:GaAs, 17 Cr:ZnTe, 18 and Mn:InAs, 19 however, materials for which the intrinsic origins of ferromagnetism are less controversial. We propose that the ferromagnetic MCD signal in Fig.…”
mentioning
confidence: 99%
“…For potential spintronic applications based on II-VI magnetic QDs, we anticipate that it is possible to further increase the magnetization and the temperature at which it vanishes. In addition to exploring a larger hole-Mn exchange coupling [22] in (II,Mn)VI QDs, it would also be advantageous to consider (II,Cr)VI QDs as there is a support for the room-temperature ferromagnetism in their bulk counterparts [27]. This work is supported by the US ONR, NSF-ECCS Career, the NRC HPC project, CIAR, and the CCR at SUNY Buffalo.…”
mentioning
confidence: 99%
“…11 and 12͒ and even at room temperature with x = 0.20. 13,14 In addition, Pekarek et al found that the transition temperature is slightly above 300 K for the ferromagnetic phase in a bulk Zn 1−x Cr x Te crystal grown by vertical Bridgman method. 15 They ascribed the ferromagnetic signal to a pure CrTe minority phase.…”
mentioning
confidence: 99%